Heme-Peroxidase 2, a Peroxinectin-Like Gene, Regulates Bacterial Homeostasis in Anopheles stephensi Midgut - Kakani, Parik; Gupta, Lalita; Kumar, Sanjeev (Frontiers in Physiology, 2020)
The dynamic nature of mosquito gut microbiome is associated with different stages of development and feeding behaviors. Therefore, mosquito gut harbors a wide range of endogenous microbes that promote numerous life processes such as, nutrition, reproduction and immunity. In addition, gut microbiota also play an important role in the regulation of Plasmodium (malaria parasite) development. Thus, understanding the mechanism of microbial homeostasis in mosquito gut might be one of the strategies to manipulate malaria parasite development. In the present study, we characterized a 692 amino acids long secreted midgut heme-peroxidase 2 (AsHPX2) in Anopheles stephensi, the major Indian malaria vector. The presence of putative integrin binding motifs, LDV (Leu-Asp-Val), indicated its peroxinectin-like nature. Phylogenetic analysis of AsHPX2 protein revealed that it is a Culicinae lineage-specific gene. RNA interference (RNAi)-mediated silencing of AsHPX2 gene significantly enhanced the growth of midgut bacteria in sugar-fed mosquitoes against sham-treated controls. Interestingly, blood-feeding drastically reduced AsHPX2 gene expression and enhanced the growth of midgut bacteria. These results revealed a negative correlation between the expression of AsHPX2 gene and gut bacterial homeostasis. We proposed that AsHPX2, being a mosquito-specific gene, might serve as a ‘potent target’ to manipulate midgut microbiota and vector competence.